The Policy Implementation in the Development of Water Front City in Senapelan District Pekanbaru - PRIHATIN, PANCA; RINALDI, KASMANTO (Jurnal Studi Pemerintahan, 2013)
Structuring urban areas, especially the Pekanbaru City, is necessary given the problem of development ofPekanbaru City is more and more complex and highly in need of a better arrangement, especiallyconcerning on the improvement of the environment (Water Front City) in Siak River surroundings. Thisis a descriptive qualitative research with population sample of the Office of Settlement and RegionalInfrastructure of Pekanbaru City, Senapelan District Government, NGOs, community leaders, andprivate parties. Data are collected through interview, observation and documentation, which is thenanalyzed using qualitative analysis technique. This research finds that the policy of the development ofWater Front City at Village Kampung Baru sub-district Senapelan Pekanbaru is not implementedoptimally. This situation can be seen through a variety of indicators related to the implementation ofdevelopment policies of Water Front City at Village Kampung Baru sub-district Senapelan Pekanbaru inthat the effect of interest policies, benefits, desire for change, the process of decision-making, implementingprograms and supporting resources have not been implemented effectively. The curbing factors inimplementing development policies in the District Water Front City Senapelan Pekanbaru are mostly dueto the lack of human resources, process of compensation and other inadequate financing, and managerialinstruments that are unsupported to the implementation of development programs of Water Front Cityat Village Kampung Baru sub-district Senapelan Pekanbaru.